Seasonal variation of fish species and genotoxic effects as a result of human activities at the Ologe Lagoon, Nigeria - Simeon Oluwatoyin Ayoola; Taiwo David Aina (Syiah Kuala University, 2017)
The fish abundance was determined by monitoring and recording the fish-catch data at the Otto Jetty in the Ologe lagoon. The diversity indices used for the purpose of this project were Species richness (S) and Shannon – Weiner index (H´). Three fish species from the lagoon were used for the micronucleus assay and nuclear aberrations; these are Tilapia guineensis, Sarotherodon melanoteron, and Chrysichthys nigrodigitatus. Diversity indices (H) obtained for the months of June, July, August and September were 2.61, 2.54, 2.54, 2.61 respectively while evenness (J) for the months were 0.64, 0.60, 0.53, 0.44 respectively. Apart from the presence of micronucleus, the genotoxicity assay also showed the presence of binucleated nucleus and blebbed nucleus. These are evidence that Ologe lagoon has a certain level of pollution, though at a minimal level. As advanced by this research work, there is great variation in fish composition and abundance in Ologe lagoon in relation to changes in the physical and chemical state of the water in the lagoon during the months of this research and this is very crucial to the biological life of the lagoon. However, anthropogenic activities should be regulated so as to prevent the level of pollution from increasing beyond tolerable limits.